Multiple cranial nerve palsy - Costa Elice, Gino (1950)
Among the most important neurological problems and greatest interest in the art, there are those who claim the collaboration of other disciplines, because they allow to understand the clinical manifestations, not as an expression of suffering of isolated systems, but as an exponent of a single disorder.